Colchicine - an effective treatment for children with a clinical diagnosis of autoinflammatory diseases without pathogenic gene variants - Tatjana Welzel; Anna L. Wildermuth; Norbert Deschner; Susanne M. Benseler; Jasmin B. Kuemmerle-Deschner (BMC, 2021)
Abstract Background Autoinflammatory diseases (AID) are rare chronic conditions with high disease burden, affecting children and adults. Clinically and genetically confirmed, AID can be effectively treated with targeted cytokine inhibition. In contrast, for patients with clinical AID symptoms without pathogenic gene variants, no treatment recommendations are available. Colchicine is approved and established as effective, safe and low-cost first-line therapy in Familial Mediterranean Fever. Up to now, efficacy data for colchicine in children with a clinical AID diagnosis without pathogenic gene variants are rare. This pilot study was performed to evaluate the effectiveness of colchicine in children with a clinical diagnosis of AID without pathogenic gene variants. Methods A pilot cohort study of consecutive children with active clinical AID without pathogenic gene variants treated with colchicine monotherapy was performed between 01/2009 and 12/2018. Demographics, clinical and laboratory characteristics were determined serially. Colchicine dosing and safety were documented. Physician estimate of disease activity was captured on visual analogue scales (VAS). Primary outcome: Complete response (PGA ≤2 plus CRP ≤0.5 mg/dL and/or SAA ≤10 mg/L) at last follow-up. Secondary outcomes: partial/no response, flare characteristics and requirement for rescue therapies. Analysis: Nonparametric comparison of disease activity measures. Results A total of 33 children were included; 39% were female. Median age at colchicine start was 3.8 years, median follow-up was 14.1 months. Clinical AID diagnoses included CAPS (24%), FMF (27%), PFAPA (43%) and unclassified AID (6%). At baseline, overall disease activity was moderate (PGA 4), inflammatory markers were elevated (CRP 12.1 mg/dL; SAA 289.2 mg/L), and 97% reported febrile flares. Outcome: 55% achieved complete response, 35% showed partial response and 58% had no febrile flares at last follow-up. Inflammatory markers (SAA: p < 0.0001, CRP: p < 0.005) and disease activity (p < 0.0001) decreased significantly. Overall, 93% of children experienced improvement of flare characteristics. Conclusion Colchicine was found to be effective and safe in children with a clinical AID diagnosis in the absence of pathogenic gene variants. Colchicine is a low-cost treatment option for non-organ threatening AID.